2006
DOI: 10.1111/j.1365-3032.2006.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling temperature‐dependent bionomics of Bemisia tabaci (Q‐biotype)

Abstract: The influence of temperature (17, 21, 25, 30 and 35 °C) on life-history traits of a Q-biotype Bemisia tabaci population on tomato is studied. Temperaturedependent relationships are characterized for immature developmental rate, immature survival, fecundity, longevity and intrinsic rate of increase. Development time vary from 20 days at 30 °C to 56 days at 17 °C and the lowest thermal threshold is estimated at 10.2 °C. The optimal temperature for immature development is 32.5 °C. Total fecundity (eggs per femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 29 publications
(40 reference statements)
8
101
2
6
Order By: Relevance
“…Yee and Toscano (1996) reported the range of 40.6 -70.6 eggs for alfalfa, broccoli, cantaloupe, zucchini and cotton at 27°C. The intrinsic rate of natural increase (r m ) of B biotype and A reared on cotton (0.1033 and 0.1010, respectively) in present study were almost equal to r m for Q-biotype of B. tabaci reared on tomato (0.106) at 25 ± 1ºC, 60 ± 5% RH and L14:D10 h (Bonato et al 2007). …”
Section: Discussionmentioning
confidence: 53%
“…Yee and Toscano (1996) reported the range of 40.6 -70.6 eggs for alfalfa, broccoli, cantaloupe, zucchini and cotton at 27°C. The intrinsic rate of natural increase (r m ) of B biotype and A reared on cotton (0.1033 and 0.1010, respectively) in present study were almost equal to r m for Q-biotype of B. tabaci reared on tomato (0.106) at 25 ± 1ºC, 60 ± 5% RH and L14:D10 h (Bonato et al 2007). …”
Section: Discussionmentioning
confidence: 53%
“…Similarly, it is possible that the high insecticide pressure within French glasshouses may have selected for group Q populations rather than group B. In addition, the developmental studies done on French group Q populations showed a greater tolerance to both hot and cold conditions than reported for group B (Bonato et al, 2007). Therefore, both extreme temperature tolerance and insecticide resistance might have favoured (alone or in combination) the development of group Q individuals to the detriment of group B individuals and could reasonably account for the predominance of group Q we observed in glasshouses in southern France.…”
Section: Discussionmentioning
confidence: 95%
“…The predominance of group Q and the putative displacement of group B, which is more sensitive to pesticide spraying, are additional pieces of evidence that human activities deeply impact the population genetics of B. tabaci in southern France. Furthermore, the putative higher tolerance of group Q populations to extreme temperature conditions (Bonato et al, 2007) can foster its further spread northward in Europe, due to better outdoor survival. These data are of primary importance for prophylactic policies against the spread of this invasive pest throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…Growth rate Invasive insects have rapid growth rates compared to natives (Labrie et al 2006, Ward andMasters 2007) A, O Preimaginal (pre-adult) development time Invasive insects have shorter preimaginal development time than natives (Cervo et al 2000, Gamboa et al 2004, Boman et al 2008, Delatte et al 2009); Invasive insects have a longer preimaginal development time than natives (Bonato et al 2007) A, E, O…”
Section: Developmentmentioning
confidence: 99%
“…Temperature tolerance Invasive insects have lower temperature tolerance than natives (Wuellner and Saunder 2003, Bonato et al 2007, Peacock and Worner 2008, Delatte et al 2009, McGrannachan and Lester 2013, Parkash et al 2014;…”
Section: Dispersalmentioning
confidence: 99%